Immunophenotypic investigation of infant acute myeloid leukemia - A. M. Popov; G. A. Tsaur; T. Yu. Verzhbitskaya; O. V. Streneva; E. V. Shorikov; L. I. Saveliev; L. G. Fechina (Онкогематология)
Aim of the study – characterization of immunophenotype in infant acute myeloid leukemia (AML). 90 patients (40 boys and 50 girls) with acute leukemia (AL) aged up to 365 days were included in the current study. AML was found more frequently in infants than in older children (26.67 % and 10.83 % respectively; p = 0.0002). Significant immunophenotypic differences were observed in patients with and without MLL gene rearrangements. Number of cases in those tumor cells expressed CD99, CD61, CD133, CD15, NG2 varied between MLL-positive and MLL-negative groups. CD61-negativity, high CD99, CD15, CD133 and NG2 expression were immunophenotypic signatures of MLLrearranged infant AML, although CD99 and NG2 had the highest diagnostic efficacy. Thus infants’ AML immunophenotype differs significantly due to the presence of MLL gene rearrangements. Diagnostic immunophenotyping of infants’ AML allows predicting presence of MLL rearrangements by either CD99 or NG2 expression.